Россия. Толкучка - Платов Александр (О России и для России, 2001)
Экземпляры: аб. Камская библиотека (20190913) / Инвентарный номер: 7468 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: П 37 / ББК: 84(2Рос=Рус)6-4